Simkania negevensis and acute cellular rejection in lung transplant recipients. (20th July 2015) - Jamal, Alainna J.; Resende, Mariangela R.; Prochnow, Taisa; McGilvray, Ian; Pilewski, Joseph M.; Crespo, Maria M.; Singer, Lianne G.; McCurry, Kenneth R.; Kolls, Jay K.; Keshavjee, Shaf; Liles, W. Conrad; Husain, Shahid
Abstract: Simkania negevensis infection has been hypothesized to play a role in lung transplant rejection. The incidence of S. negevensis infection and its association with acute cellular rejection (ACR) were determined in a prospective cohort study of 78 lung transplant recipients (LTRs) in Toronto, Canada, and Pittsburgh, USA, from July 2007 to January 2010. Simkania negevensis testing was detected by quantitative polymerase chain reaction (PCR) on bronchoalveolar lavage fluid. The relationship between S. negevensis and ACR was examined using Cox proportional hazards models and generalized linear and latent mixed models. Cumulative incidence estimates for time‐to‐ACR in S. negevensis PCR‐positive vs. PCR‐negative LTRs were 52.7% vs. 31.1% at six months and 68.9% vs. 44.6% at one yr, respectively. Although not statistically significant, there was a trend toward a higher risk of ACR among S. negevensis PCR‐positive vs. PCR‐negative LTRs in all statistical models.